Nonalcoholic fatty liver disease and risk of prostatic diseases: Roles of insulin resistance. (30th March 2021) - Zhao, Shankun; Wang, Yaoyao; Wu, Weizhou; Yang, Suqing; Feng, Lili; Tao, Fangfang; Ge, Weiwei; Shen, Maolei; Xu, Weifang
Abstract: Nonalcoholic fatty liver disease (NAFLD), the liver component of metabolic syndrome, is considered to be associated with high risk of prostatic diseases but a systematic review has not been conducted. Under a comprehensive review of the eligible clinical studies, a potential positive association between NAFLD and benign prostatic hyperplasia/prostate cancer (BPH/PCa) has been postulated. Insulin resistance and metabolic aberrations are considered to be the potential mechanism for such association. However, the relationship between NAFLD and other prostatic diseases, that is, prostatic inflammation and lower urinary tract symptoms, seems vague due to limited relevant studies in the literatures. The present review highlights that clinicians should be conscious of the detrimental effect of NAFLD on the development of BPH and PCa.